Mobile art flows. Tourism mobilities at the museum - Andrade, Pedro José de Oliveira (2018)
This texto analyses the genealogy of the historical and social phenomenon ‘mobility’,bringing about a brief discussion on the particular phenomenon of tourism mobilities, in order to provide na understanding about tourism mobilities.